PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR), INTELLECTUAL CAPITAL, KEPEMILIKAN MANAJERIAL DAN FIRM SIZE TERHADAP KINERJA KEUANGAN - NOVITA, ANNI RIZQAYANTINI (JURNAL PENDIDIKAN AKUNTANSI & KEUANGAN, 2014)
This study aims to determine the effect of corporate social responsibility, intellectual capital, managerial ownership, and firm size on the financial performance of companies. Object of research is the consumer goods sub-sectors of manufacturing company listed on the Indonesian Stock Exchange in the year 2010 to 2013. Samples used in this study were 29 companies and the techniques used are saturated samples. The method used is quantitative. The data source used in this research is secondary data in the form of annual reports obtained from the Indonesia Stock Exchange (IDX).  Results of this study indicate that CSR, managerial ownership and firm size has no effect on financial performance, while the effect of intellectual capital on financial performance.